Why Governments Prefer Spatially Segregated Settlement Sites for Urban Refugees - Kibreab, Gaim (Refuge: Canada’s Journal on Refugees, 2007)
The urbanization of Africa has been recent, rapid and notably disimllar from the pattern of urbanization that occured previously in Europe. Significantly, the urbanization of Africa has occured in the absence of structural transformation. Within this reality, refugees are viewed by African host governments as exacerbating the problems of urbanization and are most often located in government-designated and spatially segregated sites - refugee camps or settlements. Often in defiance of such policies, most refugees with urban backgrounds tend to congregate in urban centres. The case study of Sudan illustrates that even where the stay of certain refugees in urban areas may be formally regularised by governments there are nonetheless identifiable common patterns and problems arising out of and causing the spatial segregation of refugees away from urban centres. It is argued that the underlying reality of urbanization in Africa plus the protracted problems for governments created by urbanisation generally and cross-border ethnic solidarity in the case of many refugee movements in Africa, shape current hostile refugee policies towards urban refugees.